2018
DOI: 10.3906/tar-1708-56
|View full text |Cite
|
Sign up to set email alerts
|

Olive tree response to the severity of pruning

Abstract: Pruning has been advocated for several purposes: in young trees, mainly to build a framework necessary to support fruit load (Vossen, 2007;Gregoriou, 2009;Therios, 2009); in mature trees, pruning is performed to maximize sunlight exposure and to maintain the equilibrium between vegetative and reproductive functions (Sibbett, 2005;García-Ortiz et al., 2008). Other relevant objectives assigned to pruning are to reduce the severity of and/or facilitate pest and disease control (Sibbett, 2005;Tombesi and Tombesi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that the removal of nutrients by the crop is low (Rodrigues et al, 2012;Fernández-Escobar et al, 2015), which may help explain the relative success of olive cultivation in marginal growing conditions. In traditional rainfed farming systems, pruning is often used to reduce the shoot/root ratio, which keeps the remaining foliage in better watering and nutritional conditions to ensure a minimum level of productivity (Rodrigues et al, 2018). However, nowadays, particularly in irrigated and more intensive farming systems, fertilization is abundant and often excessive (Fernández-Escobar, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the removal of nutrients by the crop is low (Rodrigues et al, 2012;Fernández-Escobar et al, 2015), which may help explain the relative success of olive cultivation in marginal growing conditions. In traditional rainfed farming systems, pruning is often used to reduce the shoot/root ratio, which keeps the remaining foliage in better watering and nutritional conditions to ensure a minimum level of productivity (Rodrigues et al, 2018). However, nowadays, particularly in irrigated and more intensive farming systems, fertilization is abundant and often excessive (Fernández-Escobar, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The pruning of olive trees has a direct influence on both the tree physiology and the quality of the oil [69]. It is worth noting that in adult trees, pruning is carried out to possibly maintain the equilibrium between vegetative and reproductive functions in order to reduce the alternate bearing, and to facilitate pest and disease control as well as the harvest (Figure 3) [70,71].…”
Section: Tree Pruningmentioning
confidence: 99%
“…The pruning of olive trees has a direct influence on both the tree physiology and the quality of the oil [69]. It is worth noting that in adult trees, pruning is carried out to possibly maintain the equilibrium between vegetative and reproductive functions in order to reduce the alternate bearing, and to facilitate pest and disease control as well as the harvest (Figure 3) [70,71]. Performing hard pruning on a four-to five-year basis, as usually done in many olive groves in Salento, has a negative influence on the trees, causing shading, an irrational spatial distribution of the canopy, shorter and compact vegetation, and deadwood in the inner part of the vegetation, resulting in lower tree productivity [72], and generally it is not considered a good practice for olive [71].…”
Section: Tree Pruningmentioning
confidence: 99%
See 1 more Smart Citation
“…The average weight of wood pruning during the four years in the rejuvenation pruning treatments ranged from 180.9 to 215.5 kg tree -1 without statistical difference among them, while in the control treatment it was only 27.2 kg tree -1 . Rodriguez et al [17] reported that hard pruning in olive tree with removal of 50-70% of the foliage and performed every four years removed 2700 kg dry matter ha -1 , from which 600 kg ha -1 corresponded to leaves. The wood obtained from the pruning of rejuvenation can be used as firewood to heat the home during the cold months [18], for charcoal, utensils and toys elaboration and to build fences [19].…”
Section: Vegetative Parametersmentioning
confidence: 99%